Validation of the weakest link approach and the proposed Weibull based probability distribution of failure for fatigue design of steel welded joints. (September 2016) - Blacha, Ł.; Karolczuk, A.
Abstract: The paper describes validation process of a proposed application of the weakest link concept to fatigue life evaluation of steel welded joints. The weakest link concept was used to evaluate failure probability and the resulting fatigue lives of typical welded joints under the constant amplitude uniaxial loading. The validation of this approach involved comparison between the modeling results and experimental results. Investigation concerned butt- and double T-joints manufactured from three steel grades, the latter of which being of two thicknesses. Two assumptions for the approach have been tested: (i) applicability to joints of different geometry and (ii) ability to predict the effect of decreased fatigue life in joints with higher plate thickness. The results revealed appreciable effect of geometry on cumulative distribution function of failure, changing the kurtosis of failure distribution. Highlights: probabilistic model based on the weakest link concept was validated through comparison to fatigue test results; in general, the predicted fatigue lives compared to experimental are in the scatter band Tn = 3; failure probability distributions of steel welded joints were evaluated; geometry and volume of the welded joint were proven to have effect on the failure distribution; the distribution was illustrated through probability density functions, cumulative distribution functions and kurtosis';